Numerical methods in structural mechanics - Bittnar, Zdenek (Thomas Telford, 1996)
Aimed at undergraduate students on senior level and for graduate students, this book offers the reader an understanding of the nature and the theoretical basis of the most widely used numerical methods. It highlights the most promising directions of their future development.